Soil factors affecting growth of seedlings in logged-over tropical lowland forest in Pasoh, Negeri Sembilan, Malaysia - Mokhtaruddin, A.M.; Maswar; Majid, N.M.; Yusoff, M.K.; Hanum, I.F.; Azani, A.M.; Kobayashi, S. (Center for International Forestry Research, 2001)
Effects of soil properties on growth of young tree seedlings of Hopea odorata and Azadirachta excelsa in line and gap enrichment planting in logged-over tropical lowland forest were evaluated. At 13 months, the trees were grouped into “good” and “poor” growth based on their height increment in the previous 6 months. Organic matter content, penetration resistance, soil texture, thickness of A-horizon, Ca and Mg contents differed significantly between soils with “good” and “poor” growth. Organic matter, thickness of A-horizon, Ca and Mg contents were found to be significantly higher in “good” growth soils than “poor” ones, but penetration resistance was the reverse. Surface soils under “good” growth had lower clay content and higher sand content compared to that under “poor” growth. Favourable soil conditions for good growth were also manifested in biomass and litter accumulation. The mean dry biomass in the “good” and “poor” growth was 174 and 72 g m-2 respectively, and for dry litter 300 and 154 g m-2 respectively. Properties most limiting seedling growth performance were bulk density (mechanical resistance), depth of A-horizon and amount of clay in the surface soil. Correction of these factors is therefore important in ensuring the success of rehabilitation and reforestation of logged-over degraded forest.